The synthesis and analysis of lignin-bound Hibbert ketone structures in technical lignins. Issue 42 (11th October 2016) - Miles-Barrett, Daniel M.; Neal, Andrew R.; Hand, Calum; Montgomery, James R. D.; Panovic, Isabella; Ojo, O. Stephen; Lancefield, Christopher S.; Cordes, David B.; Slawin, Alexandra M. Z.; Lebl, Tomas; Westwood, Nicholas J.
Abstract : A detailed NMR study of lignin-bound Hibbert ketone structures and depolymerisation studies of technical lignins to yield novel aromatic compounds. Abstract : Understanding the structure of technical lignins resulting from acid-catalysed treatment of lignocellulosic biomass is important for their future applications. Here we report an investigation into the fate of lignin under acidic aqueous organosolv conditions. In particular we examine in detail the formation and reactivity of non-native Hibbert ketone structures found in isolated organosolv lignins from both Douglas fir and beech woods. Through the use of model compounds combined with HSQC, HMBC and HSQC-TOCSY NMR experiments we demonstrate that, depending on the lignin source, both S and G lignin-bound Hibbert ketone units can be present. We also show that these units can serve as a source of novel mono-aromatic compounds following an additional lignin depolymerisation reaction.